Active drag reduction of a high-drag Ahmed body based on steady blowing. (10th December 2018) - Zhang, B. F.; Liu, K.; Zhou, Y.; To, S.; Tu, J. Y.
Abstract : Active drag reduction of an Ahmed body with a slant angle of $25^{° }$, corresponding to the high-drag regime, has been experimentally investigated at Reynolds number $Re=1.7× 10^{5}$, based on the square root of the model cross-sectional area. Four individual actuations, produced by steady blowing, are applied separately around the edges of the rear window and vertical base, producing a drag reduction of up to 6–14 %. However, the combination of the individual actuations results in a drag reduction 29 %, higher than any previous drag reductions achieved experimentally and very close to the target (30 %) set by automotive industries. Extensive flow measurements are performed, with and without control, using force balance, pressure scanner, hot-wire, flow visualization and particle image velocimetry techniques. A marked change in the flow structure is captured in the wake of the body under control, including the flow separation bubbles, over the rear window or behind the vertical base, and the pair of C-pillar vortices at the two side edges of the rear window. The change is linked to the pressure rise on the slanted surface and the base. The mechanisms behind the effective control are proposed. The control efficiency is also estimated.